Arctic Ocean, polar ice - Ellsworth, Lincoln, 1880-1951 (1926)
"No. 23 Amundsen-Ellsworth 1925 Exped. The Mystery of the Polar Ice" Caption taken from Ellsworth, L., & National Americana Society. (1929). Air Pioneering in the Arctic: the Two Polar Flights of Roald Amundsen and Lincoln Ellsworth (pp. 57, No.23). New York: National Americana Society. The Mystery of the Polar Ice. Transpolar Flight of the Norge, May, 1926.